2023
DOI: 10.1097/md.0000000000033177
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer risk in East Asian patients with Helicobacter pylori infection: A systematic review and meta-analysis

Abstract: Background: The aim of this systematic review and meta-analysis was to assess the relationship between H pylori infection and colorectal cancer risk in East Asian patients.Methods: Two researchers independently searched for relevant studies in the PubMed, Cochrane, and Embase databases from inception up to April 2022. A meta-analysis was then performed to calculate pooled odds ratios (ORs) with corresponding 95% confidence intervals (CIs) using a random effects model.Results: Nine studies involving 6355 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Hp is an infectious gram-negative pathogenic bacterium that can be transmitted through fecal-oral, oral-oral, and gastric-oral routes, and the incidence of H. pylori infection varies from region to region and from lifestyle to lifestyle [9] .The inflammatory substances, lipase proteins and toxic substances secreted by Hp can damage the gastric barrier leading to chronic gastritis, peptic ulcer, gastric cancer and extra-gastrointestinal diseases [10] . In recent years, it was reported that the prevalence of Hp infection was positively correlated with the prevalence of hypertension in Chinese adults [11,12] , which is a risk factor for cardiovascular and ocular diseases, while H. pylori infection can increase homocysteine levels [4,13,14] , which in turn is an important risk factor for cardiovascular and cerebrovascular pathogenesis, as well as an independent risk factor for osteoporosis In addition, the poor living conditions, irregular living habits, and stressful life of workers make them more likely to be infected with Hp and highly susceptible to related diseases, therefore, workers should be considered as a key concern, so it is urgent to study the risk factors of H. pylori infection and H hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Hp is an infectious gram-negative pathogenic bacterium that can be transmitted through fecal-oral, oral-oral, and gastric-oral routes, and the incidence of H. pylori infection varies from region to region and from lifestyle to lifestyle [9] .The inflammatory substances, lipase proteins and toxic substances secreted by Hp can damage the gastric barrier leading to chronic gastritis, peptic ulcer, gastric cancer and extra-gastrointestinal diseases [10] . In recent years, it was reported that the prevalence of Hp infection was positively correlated with the prevalence of hypertension in Chinese adults [11,12] , which is a risk factor for cardiovascular and ocular diseases, while H. pylori infection can increase homocysteine levels [4,13,14] , which in turn is an important risk factor for cardiovascular and cerebrovascular pathogenesis, as well as an independent risk factor for osteoporosis In addition, the poor living conditions, irregular living habits, and stressful life of workers make them more likely to be infected with Hp and highly susceptible to related diseases, therefore, workers should be considered as a key concern, so it is urgent to study the risk factors of H. pylori infection and H hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past three decades, our understanding of Helicobacter pylori ( H. pylori ) has significantly advanced, revealing its association with various extragastric disorders encompassing gastrointestinal tumors, 1–3 hepatobiliary diseases, 4,5 respiratory system diseases, 6 cardiovascular diseases, 7,8 metabolic disorders, 9 and hematologic diseases 10 . This association can be attributed to the chronic and persistent nature of H. pylori infection, which induces chronic inflammation and immune responses.…”
Section: Introductionmentioning
confidence: 99%